DESCRIPTIONOF KNOWLEDGE ABOUT HEART DISEASE OF PATIENT WITH PULP NECROSISIN BADUNG DISTRICT GENERAL HOSPITAL IN 2016 - Ni Putu Adnyaniswari; I Nyoman Gejir; I Nyoman Wirata (Jurnal Kesehatan Gigi (Dental Health Journal), 2016)
Pulp necrosis shown to be associated with heart disease. The spread of diseases of the teeth to other organs can be explained by the theory of focal infection. The impact of dental disease on the heart may be a coronary heart disease, inflammation of the heart muscle and valves. This study aims to describe the knowledge about heart disease in patientswith pulp necrosis in Badung District General Hospital 2016. This study is descriptive study. The sample was 50 people. The result of this research is the level of knowledge about heart disease in the category fail to reach 5 people (10%) and the majority of respondents in this category junior high school education. Whereas in the excellent category reached 16 people (32%) and the majority of respondents in this category educated to degree. The average knowledge about heart disease in patients with necrotic pulp was 67,6 with enough categories. Suggestions in this study is the dental and oral health professionals are expected to increase promotional efforts through therapeutic communication to all patients who visit and give an explanation to patients with necrotic pulp so that patients understand the consequences caused by the necrosis of the pulp is mainly to do with heart disease.